Advancing climate-change goals: From reactive to proactive systemic integration - Julien Chaisse; Arjun Solanki (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2022)
Can countries fulfill their obligations under international environmental agreements in the presence of international investment agreements or vice versa? This Perspective offers recommendations for arbitrators and countries to harmonize their climate goals and investment obligations by moving from a strictly disciplinary view of investment law through the lens of general international law.
Keywords: 330